2006
DOI: 10.1007/s00167-005-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

Minimal rotation aberrations cause radiographic misdiagnosis of trochlear dysplasia

Abstract: Radiologic criteria are commonly used to diagnose femoral trochlear dysplasia causing patellofemoral (sub)luxations. A dysplastic trochlea can be identified on conventional radiographs when the line of the trochlear groove crosses the anterior border of one or both condyles. The aim of this study was to establish the influence of rotation on the precision of these radiographic criteria as classified on a true lateral conventional radiograph. In a radiological in vitro study using two different distal femurs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…On a lateral knee radiograph, the “crossing sign” was described, a geometrical abnormality at the cranial portion of the trochlea that prevents proper engagement of the patella during the early phases of knee flexion [22]. However, two-dimensional imaging may lead to misinterpretation of the patellar morphology [7]. Therefore, 3.0T MRI was used in our study for a more detailed analysis of cartilage, tendon and bone marrow and found similar results; individuals with lower trochlear depth showed significantly increased patellofemoral degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a lateral knee radiograph, the “crossing sign” was described, a geometrical abnormality at the cranial portion of the trochlea that prevents proper engagement of the patella during the early phases of knee flexion [22]. However, two-dimensional imaging may lead to misinterpretation of the patellar morphology [7]. Therefore, 3.0T MRI was used in our study for a more detailed analysis of cartilage, tendon and bone marrow and found similar results; individuals with lower trochlear depth showed significantly increased patellofemoral degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…On plain radiographs, a sulcus angle >150° indicates trochlear dysplasia. However, two-dimensional imaging underestimates the angle and shows substantial differences of about 20° to more accurate MR measurements [710]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, classification of the trochlear dysplasia on radiographs to determine the severity level, was shown to be a difficult issue [3,21]. During whole lateral knee radiography, even a 58 rotation mistake has been reported to cause false positive or negative values for trochlear dysplasia [16]. Because the dysplastic area on the trochlea is commonly localized at the anterior or proximal aspects, this dysplastic area may not be seen on tangential patellar radiographs taken at 308 or lower flexion [5].…”
Section: Discussionmentioning
confidence: 99%
“…Until today radiographic outcome after trochleoplasty was determined on plain radiographs only [32,39]. As it was shown that minimal rotation aberrations cause misdiagnosis of trochlear dysplasia on plain radiographs [21], it was the aim of this study to describe the trochlear morphology and the patellofemoral relation before and after trochleoplasty on CT images.…”
Section: Discussionmentioning
confidence: 99%